Tingkat Korosifitas Air Permukaan Hilir Rawa Pening pada Musim Kemarau dan Penghujan - Purwono, Purwono; Oktiawan, Wiharyanto; Istirokhatun, Titik; Nurfaiz, Agus (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2020)
Corrosion is an important factor that can affect the quality of air used by humans. This has an impact on health and economic factors, damage to air distribution equipment. The level of corrosivity of surface water as raw water for drinking water is important to be examined before the water enters the processing process or other uses such as hydroelectric power (PLTA). This study aims to measure the level of water corrosivity on the surface of the Pening swamp during the dry and rainy seasons in 2018. Taking air samples on the surface of the Pening swamp, then carrying out laboratory tests on the parameters of air corrosivity. The results showed that the downstream surface of the Pening swamp was not corrosive in terms of pH, temperature, TDS, and chloride parameters. The pH value in the dry season (J1) is 7.00, while in the rainy (J2) it is 7.77 and is non-corrosive. The temperature values are 28.6oC and 29.3oC in the rainy and dry seasons, respectively. The TDS measurement results in the dry season are lower than the rainy season by a difference of 12 mg / l. In the dry season it is 141 mg / l and the rainy season is 153 mg / l. This increase probably came from geological material (geological material) such as rocks and soil around the Pening Swamp Lake. Other sources of TDS include urban land, road workers, agricultural land and pasture. Human activities also increase in the increase of TDS in water including domestic activities (bathing and washing), trade, and industry. Chloride levels were 2.19 mg / l and 3.19 mg / l. This research has implications for the users of Sungai Pening Swamp. The corrosivity of air measurement is also by microbiological parameters which need to be investigated further.